Heritage designation and scale: a World Heritage case study of the Ningaloo Coast. Issue 3 (15th March 2016) - Jones, Tod; Jones, Roy; Hughes, Michael
Abstract: As heritage research has engaged with a greater plurality of heritage practices, scale has emerged as an important concept in Heritage Studies, albeit relatively narrowly defined as hierarchical levels (household, local, national, etcetera). This paper argues for a definition of scale in heritage research that incorporates size (geographical scale), level (vertical scale) and relation (an understanding that scale is constituted through dynamic relationships in specific contexts). The paper utilises this definition of scale to analyse heritage designation first through consideration of changing World Heritage processes, and then through a case study of the world heritage designation of the Ningaloo Coast region in Western Australia. Three key findings are: both scale and heritage gain appeal because they are abstractions, and gain definition through the spatial politics of interrelationships within specific situations; the spatial politics of heritage designation comes into focus through attention to those configurations of size, level and relation that are invoked and enabled in heritage processes; and researchers choice to analyse or ignore particular scales and scalar politics are political decisions. Utilising scale as size, level and relation enables analyses that move beyond heritage to the spatial politics through which all heritage is constituted.